PENGARUH PRESTASI BELAJAR DAN ADVERSITY QUOTIENT TERHADAP PENYELESAIAN SKRIPSI MAHASISWA JURUSAN PENDIDIKAN EKONOMI FAKULTAS EKONOMI UNP - Hazimatul Ulfah; Tri Kurniawati; Efni Cerya (Jurnal Ecogen, 2018)
Abstract: This study aims to examine the effect of learning achievement and adversity quotient on the completion of the thesis of economic education students in the economic faculty of Padang State University. This research is a descriptive study. The population in this study were students of economic education who graduated in June, September and December 2018. This study used primary data. The analytical method used is multiple regression analysis using SPSS version 25. The results of this study indicate that 1) Learning achievement has a positive and significant effect on the completion of the thesis of economic education students with a significance value of 0.014 <0.05 2) Adversity Quotient has a positive and significant effect towards completion of the thesis of economic education students with a significant value of 0.012 <0.05 3) Learning achievement and Adversity Quotient together have a positive and significant effect on the completing of student thesis with a significance value of 0.000 <0.05.Keywords: learning achievement, adversity quotient and completing of  the thesis